ADAB DAN KARAKTER GURU-MURID: REFLEKSI PENDIDIKAN ISLAMI DALAM SURAT KAHFI DAN SURAT LUQMAN - Rifqan Hidayat; Mahyuddin Barni; Ali Muammar ZA (CV. ADIBA AISHA AMIRA, 2025)
Teachers and students are the main elements in the complementary educational process. The Qur'an and Hadith provide a comprehensive conceptual foundation regarding the roles, characters, and manners of both in learning. This research aims to explore the concept of teachers and students from the perspective of the Qur'an and Hadith, especially through the study of Surah Al-Kahfi verses 60-82 and Surah Luqman verses 13-19. The method used is content analysis with a thematic interpretation approach (maudhu'i). This study found that Prophet Khidir and Prophet Moses became ideal representations of teachers and students, where Prophet Khidir reflected wisdom, patience, and competence, while Prophet Moses showed tenacity, humility, and discipline in learning. In addition, Surat Luqman highlighted manners such as honesty, humility, and a sense of responsibility that teachers and students must have to create a conducive learning process. This research emphasizes the importance of integrating the values of the Qur'an and Hadith in education to form a generation with noble character and knowledge. By understanding and applying these principles, the educational process not only produces intelligent individuals, but also contributes to the social and spiritual harmony of society.